Low-pressure gas nitriding of AISI 304 austenitic stainless steel: reducing the precipitation of chromium nitrides - Wenzhi Xie; Yunxia Chen; Dazhi Chen; Yang Yang; Chengsong Zhang; Guodong Cui; Yixue Wang (Materials Research Express, 2020)
In this study, low-pressure gas nitriding (gas pressure of 0.01 MPa) was conducted to produce a thicker nitrided layer with high hardness and anti-corrosive properties on AISI 304 austenitic stainless steel. The effects of nitriding temperature and duration on the microstructure and surface property of nitrided layers were systematically evaluated by using optical microscope, X-ray diffraction, elemental analysis, microhardness test and potentiodynamic polarization tests. The samples were also treated under conventional gas pressure of 0.1 MPa for comparison. The results show that the low-pressure gas nitriding could restrain the precipitation of chromium nitrides effectively, which is beneficial for obtaining a thicker nitrided layer. Although the activation energy of nitrogen diffusion for low-pressure nitriding (220 kJ mol ^−1 ) is higher than that for the atmospheric pressure nitriding (196 kJ mol ^−1 ), the thickness of nitrided layers for low pressure nitriding could reach to a comparable value as that for the conventional atmospheric pressure nitriding. More importantly, the surface toughness and corrosion resistance of nitrided layers could be improved by low-pressure nitriding, which is mainly attributed to the optimized nitrogen content in nitrided layers and the reduced precipitation of chromium nitrides under low-pressure.